Sulfonated Compounds Bind with Prostatic Acid Phosphatase (PAP248–286) to Inhibit the Formation of Amyloid Fibrils. Issue 6 (11th June 2018) - Zhang, Tingting; Yang, Haikui; Yang, Zichao; Tan, Suiyi; Jin, Jiabin; Liu, Shuwen; Zhang, Jiajie
Abstract: The peptide segment of prostatic acid phosphatase (PAP248–286 ) aggregates to form SEVI (semen‐derived enhancer of virus infection) amyloid fibrils. These are characteristic seminal amyloids that have the ability to promote the effect of HIV infection. In this paper, we explore the binding of sulfonated compounds with PAP248–286 through an in silico study. Three derivatives of suramin, NF110, NF279, and NF340, are selected. All of these sulfonated molecules bind to PAP248–286 and alter the conformation of the peptide, even though they have various structures, sizes, and configurations. The compounds bind with PAP248–286 through multiple interactions, such as hydrogen‐bonding interactions, hydrophobic interactions, π–π stacking interactions, and electrostatic interactions. However, NF110, which has an X‐shaped configuration, has the highest binding affinity of the three derivatives investigated. We also perform surface plasmon resonance and a Congo red assay to validate the results. The interactions between PAP248–286 and the sulfonated compounds are proposed to depend on the orientations of the sulfonate groups and the specific configurations of the compounds instead of the number of sulfonate groups. NF110 molecules occupy the exposed binding sites of PAP248–286, blocking interactions between the peptides. Therefore, these compounds are important in inhibiting the aggregation of PAP248–286 . Herein, we provide useful information to develop new efficient microbicides to antagonize seminal amyloid fibrils and to block HIV transmission. Abstract : Blocking HIV : The peptide segment of prostatic acid phosphatase (PAP248–286 ) aggregates to form SEVI (semen‐derived enhancer of virus infection) amyloid fibrils. These are characteristic seminal amyloids that have the ability to promote the effect of HIV infection. Herein, we explore the binding of sulfonated compounds (NF110, NF279, and NF340) with PAP248–286 through an in silico study.